Edukasi tentang Stabilitas Ekstrak Buah Parijoto sebagai Counterstain pada Pewarnaan Gram Berdasarkan Variasi Suhu - Indah Sari (IKesT Muhammadiyah Palembang, 2026)
Gram staining is a differential staining procedure that divides bacteria into Gram-positive and Gram-negative groups. Safranin is one of the dyes used in Gram staining. The toxicity and health hazards posed by the use of safranin dye have been widely reported, particularly the dangers of dye contamination originating from synthetic dye waste. The use of synthetic dyes is very dangerous because it can trigger cancer, kidney and liver damage. Anthocyanins are natural pigments that have the potential to be used as dyes, including in laboratory applications such as Gram staining. Gram staining is an important technique in bacterial classification, which usually uses synthetic dyes such as safranin to detect Gram-negative bacteria. However, the use of such synthetic dyes can have adverse environmental impacts, so alternative natural dyes that are more environmentally friendly are needed. Parijoto fruit (Medinilla speciosa) is red and contains anthocyanins. Anthocyanins have low stability to the effects of heat. The use of natural dyes can reduce synthetic dye waste in bacterial staining. However, natural dyes are susceptible to temperature. The method used is education using learning posters as well as pre- and post-tests. The main focus of the activity is to increase understanding and knowledge. The participants of the activity were 6 laboratory staff of Ar-Rasyid Islamic Hospital, Palembang, who had received the education. The evaluation results of the pre-test and post-test scores of the educational activity showed an increase, which means that the laboratory staff of Ar-Rasyid Islamic Hospital, Palembang, had a better understanding and increased knowledge regarding the education on the Stability of Parijoto Fruit Extract as a Counterstain in Gram Staining Based on Temperature Variations.